PEMANFAATAN BIG DATA UNTUK LITERASI DIGITAL MAHASISWA BANDUNG (Lembaga Penerbitan Universitas Esa Unggul, 2021)
This study aims to determine the use of big data for digital literacy by Bandung students. Thisresearch method uses a qualitative approach with a descriptive method. The technique indetermining the informants that the researcher uses is the purposive sampling technique so thatthe researchers get research informants consisting of eight key informants, namely ten studentsfrom several campuses in Bandung. The results showed that: 1) Ability, Bandung students havethe ability to use big data as a digital literacy material. 2) Motivation, Bandung students aremotivated to learn and use big data because it is considered more economical, effective andefficient. 3). Barriers, Bandung students experience infrastructure barriers that are not yetoptimal